Enhancing information axiom and developing an axiomatic design based macroergonomics framework for manufacturing companies - Gündüz, Ömer. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
This study has three main goals: first, to redefine the “information axiom”, so it is applicable to ergonomic designs; second, to examine the information axiom on the cost associated with design and decision-making; and third, to develop an axiomatic design based macroergonomic framework for manufacturing companies to improve employee performance, health, safety, and overall company performance. For the stated objectives, in the light of existing literature, the “information axiom” was subjected to a rigorous evaluation. Information axiom proved to be inadequate for ergonomic designs and the existing formula was put into a new form to overcome this shortcoming. Going further, it has also been proven that information axiom does not minimize the cost associated with designs, and it has been reformulated to address this shortcoming. For the macroergonomic framework development, a Macroergonomic Evaluation Questionnaire (MEQ) was first created using the literature and expert opinions. As a result, a framework has been created for the manufacturing sector that can assist in decision-making. The usability of the formula was demonstrated in this way with a case study. In summary, this study makes two main contributions to the “information axiom”, one of the two axioms of axiomatic design: (1) The information axiom was reformulated to be applicable to ergonomic designs; and (2) the information axiom is reformulated to minimize potential costs in design and decision making. Finally, the information axiom formula reconstructed in the second phase has been successfully used to create a macroergonomic program framework for companies.
Keywords: Composite construction.; Structural optimization.; Human engineering.